Preparation of pan bread enriched with quinoa flour (Research, Society and Development, 2025)
This study aimed to evaluate the effect of partially replacing wheat flour (WF) with quinoa flour (QF) on the physicochemical characteristics of loaves of bread. Six formulations were prepared with partial replacement of WF by QF in the following proportions: F1 (100:0), F2 (95:5), F3 (90:10), F4 (85:15), F5 (80:20), and F6 (70:30), respectively. The moisture content, water activity (Wa), and instrumental color of the flours were analyzed, as well as the weight loss after baking (WLAB), moisture, Wa, specific volume (SV), texture, and color of the crust and crumb of the bread. The results indicated that the flours had moisture content between 12.0 and 13.0%, within legal limits, and Wa varied between 0.53 and 0.64, considered low, which hinders microbial growth. QF had a hue angle of 92.09, tending towards light yellow, while WF had 90.29, tending towards white. The preparation of bread with increasing amounts of QF did not significantly alter the SV (3.44 to 4.16 cm³/g), but reduced the Wa (from 0.94 to 0.93) and increased the moisture (from 37.47% to 40.88%), WLAB (from 7.69% to 8.51%), and hardness (from 300 gf to 700 gf). In addition, it intensified the brown color of the crust and light-yellow color of the bread crumb. The replacement of up to 20% of WF with QF (F5) did not influence SV, hardness, and crumb color, making it a viable alternative for the production of bread with higher nutritional value potential.